Exchangeable Ca2+ content and soil aggregate stability control the soil organic carbon content in degraded Horqin grassland. (January 2022) - Yao, Yuan; Chen, Junda; Li, Fei; Sun, Mingwei; Yang, Xuechen; Wang, Gui; Ma, Jianying; Sun, Wei
Highlights: Soil available phosphorus content positively affected microbial C use efficiency. Exchangeable Ca 2+ and Mg 2+ loss weakened physico-chemical protection of SOC. Grassland degradation enhanced SOC loss via weakening physico-chemical protection of SOC. An increase in microbial C use efficiency and decrease in microbial biomass mitigated SOC loss. Abstract: Grasslands store 20–30% of global soil organic carbon (SOC) but a majority of grasslands are suffering degradation accompanied by SOC loss. SOC stock is determined by the balance between C input from plants and C output from microbial decomposition, but the relative importance of these factors in controlling SOC and the stabilization mechanisms of SOC are poorly understood. Here, we investigated the main factors influencing SOC loss along a grassland degradation gradient in the Horqin grassland, including non-degraded (ND), lightly degraded (LD), moderately degraded (MD), and severely degraded (SD) grasslands. The contents of SOC, TN and TP at the ND and LD sites were significantly higher than those at the MD and SD sites. Plant aboveground, belowground and litter biomass significantly decreased with the intensification of degradation. Compared to the ND site, the mean weight diameter of soil aggregates decreased by 8.70%, 17.39% and 26.1% at the LD, MD and SD sites, respectively. Exchangeable Ca 2+ and Mg 2+ contents also decreased along the degradation gradient. Moreover, the results of structural equation modeling indicated that grassland degradation reduced plant biomass, resulting in an increase in soil available phosphorus content, thus causing less energy losses for microbes through their deployment of extracellular enzymes, eventually leading to an increase in microbial carbon use efficiency. Correlation analysis also confirmed that microbial carbon use efficiency was positively correlated with the ratio of G + /G - . The results of boosted regression tree model suggested that exchangeable Ca 2+ and mean weight diameter were the two most influential factors on SOC among the 13 studied variables. Stabilization mechanisms linked to chemical stabilization by polyvalent cations and soil aggregation were the most important controlling factors on SOC content during grassland degradation. In summary, although microorganisms mitigated soil carbon loss to some extent by decreasing their total biomass and increasing their carbon use efficiency, the weakened physical protection of SOC resulted in SOC loss during grassland degradation.